Relationship between Meta-Technology Ratios and Varietal Differences in Date Production (Case Study of Sistan and Baluchestan, Iran) - Shahram Saeedian; Mahmoud Sabouhi Sabouni; Javad Shahraki; Ebrahim Moradi; Mohammad Sepahi (International Journal of Agricultural Management and Development, 2013)
This paper uses the concept of Meta-frontier to investigatethe relationship between Meta Technology Ratios (MTR)and different varieties in datepalms including; Mazafati, Rabiand Zardan that are produced widely in Sistan and Baluchestanprovince of Iran. We used a stratified sampling of 300 datefarmers of this province in 2010, 2011 and 2012 and estimateda stochastic production frontier using pooled data. Then,stochastic production frontiers were estimated for each variety,separately. At the end, the meta-frontier parameters wereobtained to estimate the Meta technology ratio. Results showedthat the estimated mean values of technical efficiency for thepooled frontier, variety group frontiers and Meta frontier acrossall data were 0.558, 0.543 and 0.0014, respectively. The valueof Meta technology ratio was 0.407 for Mazafati variety, 0.432and 0.507 for Rabi and Zardan varieties respectively. Mazafatihad the lowest MTR while, Zardan and Rabi varieties aremore closed together. Surprisingly, Mazafati had the lowesttechnical efficiency with respect to group frontier and Metafrontier.The estimated average technical efficiencies withrespect to group frontiers for Mazafati, Zardan and Rabi are:0.518, 0.520 and 0.592, respectively; while Mazafati is kind ofdate which is the most exported variety.